1991
DOI: 10.1200/jco.1991.9.10.1871
|View full text |Cite
|
Sign up to set email alerts
|

Intensive chemotherapy with cyclophosphamide, carmustine, and etoposide followed by autologous bone marrow transplantation for relapsed Hodgkin's disease.

Abstract: Fifty-six consecutive patients with advanced Hodgkin's disease considered incurable with further conventional chemotherapy were entered into a protocol that included high-dose cyclophosphamide (7.2 g/m2), carmustine (BCNU; 0.6 g/m2), and etoposide (VP16-213; 2.4 g/m2) (CBV) followed by autologous bone marrow transplantation (BMT). Prior combination chemotherapy had failed in all the patients, and all but five had been previously treated with both mechlorethamine, vincristine, procarbazine, and prednisone (MOPP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
127
1
1

Year Published

1996
1996
2006
2006

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 200 publications
(133 citation statements)
references
References 0 publications
4
127
1
1
Order By: Relevance
“…In some studies, a prognostic score has been defined based on the selection of patient groups with a significantly different outcome after HDCT [7,[30][31][32]. Moskowitz et al [33] stratified three groups of patients treated with HDCT on the basis of three adverse prognostic factors (extranodal disease, B symptoms, and initial duration of response less than 1 year).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some studies, a prognostic score has been defined based on the selection of patient groups with a significantly different outcome after HDCT [7,[30][31][32]. Moskowitz et al [33] stratified three groups of patients treated with HDCT on the basis of three adverse prognostic factors (extranodal disease, B symptoms, and initial duration of response less than 1 year).…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of refractory or relapsed disease has been investigated extensively and high-dose chemotherapy (HDCT) with autologous stem cell support has become the standard protocol in patients with chemo-sensitive disease after induction therapy. Indeed, several nonrandomized studies [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] have suggested a better outcome for patients receiving HDCT. These results have been confirmed by two randomized studies [18,19] comparing a single course of HDCT to conventional chemotherapy in chemo-sensitive patients.…”
Section: Introductionmentioning
confidence: 99%
“…31 Of the various prognostic factors identified for long-term disease-free survival in high-dose chemotherapy trials, one of the most frequently found is the chemosensitivity of HD at the time of transplantation. 16,24,[27][28][29][30] Salvage chemotherapy before BMT could therefore play an important role in the curability of patients with primary refractory or relapsed HD.We report here the results of a phase II trial of the VIP regimen for patients in whom intensification was envisaged early on in the course of therapy. This treatment was offered in unselected heavily pre-treated patients with poor prognosis Hodgkin's disease who were potentially eligible (aged less than 60 year, no prior extensive bone marrow irradiation and no medical contradiction) for intensive ther-…”
mentioning
confidence: 99%
“…23 Prognostic factors allowing the identification of a subgroup of patients who would particularly benefit from highdose therapy have been extensively sought. 16,24,[27][28][29][30] Discrepancies persist regarding their legitimacy probably due to non-homogeneous patient characteristics and selection in the different cohorts studied. 31 Of the various prognostic factors identified for long-term disease-free survival in high-dose chemotherapy trials, one of the most frequently found is the chemosensitivity of HD at the time of transplantation.…”
mentioning
confidence: 99%
See 1 more Smart Citation